Pearl merchants of the Gulf and their life in Bombay - Albedwawi, Saif (Proceedings of the Seminar for Arabian Studies, 2017)
Many merchants from the Gulf States relocated to Bombay (now renamed Mumbai) during the nineteenth and early twentieth centuries, and spent the rest of their lives there. My paper will discuss the activities of merchants from the Arab Gulf States in Bombay, mainly specializing in pearls, particularly Дājjī MuΉammad ΚAlī Zainal from Jeddah, and Jāsim Āl Ibrāhīm from Kuwait. The paper is intended to shed light on the lives of these merchants, and illustrate how they interacted with Indian society. It will illustrate mercantile connections between the Gulf and Bombay and characterize the growth of family-based trading networks in the western Indian Ocean region at the height of the pearling industry.